Preparation method of multi-scale SiC particle heterostructure reinforced magnesium-based composite material

By adding Y elements to the magnesium alloy to generate Al2Y second phase and multi-scale SiC particles to form heterostructure, the problem of low modulus of magnesium alloy is solved, significantly improving the modulus and strength of the material, and improving its application potential in the aerospace field.

CN119640084AActive Publication Date: 2025-03-18SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411870770.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The modulus of existing magnesium alloy materials is relatively low, and it is difficult to significantly improve their elastic modulus and strength through chemical composition regulation, limiting their weight loss effect in aerospace and other fields.

Method used

By adding trace Y elements to generate an in-situ self-generated Al2Y second phase, combined with multi-scale SiC particles to form a heterostructure, and prepared by stirring casting, forming a "in-situ self-generated nanoscale precipitation phase Al2Y + added SiC reinforcement" dual-enhanced body configuration, which enhances the modulus and strength of the material.

Benefits of technology

It significantly improves the modulus and strength of magnesium-based composite materials, improves its mechanical properties, and expands its application range in aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640084A_ABST
    Figure CN119640084A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, and belongs to the field of metal-based composite materials and preparation thereof. According to the preparation method, an in-situ authigenic second phase generated by rare earth elements is added, micron-scale, submicron-scale and nano-scale SiC reinforcement particles form a heterostructure formed due to size difference, and after a subsequent plastic deformation process, the multi-scale reinforcement particles form a heterostructure with a layered distribution characteristic; the effects of second phase strengthening, reinforcement particle strengthening and heterostructure strengthening are generated, and meanwhile the modulus and strength of the magnesium-based composite material are improved. And moreover, a stirring casting mode is adopted for preparation, the production process is shortened, the production cost is reduced, the high-modulus and high-strength magnesium-based composite material is prepared, and the preparation method has important significance in promoting application of the high-performance magnesium-based composite material and expanding the application range of the magnesium-based composite material in the fields of automobile industry, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal-based composite materials and preparation thereof, and specifically relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material. Background Art

[0002] Magnesium alloy has low density (density ~1.8g / cm 3 ) and high specific strength are widely used in aerospace, automobile and other fields. However, since the modulus of magnesium alloy is only 45GPa, which is significantly lower than the elastic modulus of Al alloy (70GPa), and the density of Al alloy is about 1.5 times that of magnesium alloy (2.7g / cm 3 ), under the design conditions of the same stiffness, the weight reduction effect of using magnesium alloy instead of Al alloy is only 10-20%, which is not significant. Therefore, the development of high modulus and high strength magnesium alloy is conducive to improving the weight reduction effect of magnesium alloy structural parts, which has become one of the key issues that need to be solved in the application field of magnesium alloy materials.

[0003] As an emerging material system, heterogeneous structural materials show mechanical properties superior to homogeneous materials through changes in composition, phase and microstructure, such as layered structure, gradient (composition, grain or texture, etc.) structure, bimodal structure, harmonic structure, etc. Its structural design is inspired by natural materials such as shells and bamboo in nature. The three-dimensional spatial distribution, geometric shape, scale and other characteristics of the material are designed, and a variety of materials are used in the overall manufacturing process to form high-performance, super-performance and multi-performance materials and integral components with heterogeneous internal structure and regular distribution. According to the structural characteristics, heterogeneous heterogeneous materials can be divided into the following three categories: the first category is heterogeneous materials formed by the difference in material grain size based on the Hall-Patch effect, mainly including gradient nanostructured materials, bimodal structure materials, core-shell structure materials, etc. The second category is a dual-phase structure material formed by the difference in crystal structure due to phase change. The third category is a layered heterogeneous material formed by different hardness or size of the components. Among them, the layered structure material is composed of different hardness materials of different components or different components with large differences in size. The components show the characteristics of layered distribution and are composed of different layered components superimposed on each other. The preparation methods of layered structural materials generally include plastic deformation, plastic deformation + annealing, powder metallurgy + annealing, etc.

[0004] The elastic modulus of magnesium alloy is different from its strength and plasticity. It is difficult to improve it by regulating the chemical composition, phase type and distribution, grain size, etc. At present, the more effective way is to add high modulus reinforcement particles to improve the elastic modulus of magnesium alloy. SiC particles are stable ceramic materials with high hardness and strength. At the same time, their production cost is low, and they are easy to prepare and secondary process. They are ideal reinforcements for magnesium-based composites. Related studies have shown that SiC particles can be added to some composite materials as reinforcements to improve and enhance the performance of alloy materials, which can improve their comprehensive performance and thus expand the application range of magnesium alloys. In addition, how to achieve continuous and rapid production of magnesium-based composite materials is another problem faced by this field. Among the various preparation methods of metal-based composite materials, the stirring casting method has the characteristics of low cost and large-scale production, and can achieve low-cost, short-process industrial production.

[0005] Based on this, the present invention provides a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, in which rare earth elements are introduced through component design to generate an in-situ self-generated second phase, and a heterogeneous structure with size differences is formed by micron, submicron, and nanometer SiC particles, and a heterogeneous structure with layered distribution characteristics is formed through a subsequent plastic deformation process, thereby producing second phase strengthening, reinforcement particle strengthening and heterogeneous structure strengthening effects, while improving the modulus and strength of the magnesium-based composite material, and adopting a stirring casting method for preparation, which shortens the production process, reduces production costs, prepares a high modulus and high strength magnesium-based composite material, and expands the application range of the magnesium-based composite material. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material in view of the problems existing in the prior art.

[0007] First, the present invention generates an in-situ self-generated Al2Y second phase by adding a trace amount of Y element, thereby improving the modulus and strength of the material; wherein, the in-situ self-generated nanoscale precipitation phase Al2Y has a high modulus, and based on the Hashin-Shtrikman elastic theory model, it can synergistically improve the modulus of the material with the external high modulus SiC reinforcement particles, and has a "in-situ self-generated nanoscale precipitation phase Al2Y + external SiC reinforcement" dual reinforcement configuration, which significantly improves the modulus of the magnesium-based composite material;

[0008] Secondly, by adding micron, submicron, and nanometer SiC particles of different particle sizes, the modulus of the material is improved by adding reinforcement particles, and the layered heterogeneous structure formed by the size difference of multi-scale SiC particles is formed to improve the strength of the material;

[0009] Thirdly, by blowing and stirring the smelting process and ultrasonic treatment, the SiC particle reinforcement can be suspended inside the melt, which improves the dispersion and uniformity of the composite ingot reinforcement particles and further enhances the heterogeneous structure strengthening effect of the SiC particles.

[0010] Finally, through plastic deformation, the SiC particles are further dispersed evenly, and the micron and nanometer SiC reinforcement particles show a layered distribution characteristic of "coarse, fine, coarse, fine" along the extrusion direction. Submicron SiC transitions between coarse and fine layers to form a heterogeneous structure with layered distribution characteristics, which further enhances the strengthening effect of the SiC particle heterogeneous structure. Through this preparation method, magnesium-based composite materials with high modulus and high strength can be prepared.

[0011] The purpose of the present invention can be achieved by the following scheme:

[0012] The present invention provides a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, comprising the following steps:

[0013] S1, ball-milling and mixing micron-sized, submicron-sized and nanometer-sized SiC particles with Al powder particles to obtain SiC-Al mixed powder, and then cold-pressing to obtain SiC-Al composite powder prefabricated blocks;

[0014] S2, weighing other raw materials according to the alloy ratio, smelting, adding the SiC-Al composite powder prefabricated block into the smelted melt to continue smelting, and then casting to obtain a composite material ingot; the other raw materials include Mg single substance, Al single substance, and Mg-Y master alloy;

[0015] S3. The composite material ingot is homogenized and hot extruded to obtain a multi-scale SiC particle heterostructure reinforced magnesium-based composite material.

[0016] As an embodiment of the present invention, in step S1, before ball milling, the SiC particles and Al powder of micron, submicron and nanometer scales are ultrasonically cleaned, and the oil stains and impurities on the surface of the particles are cleaned with anhydrous ethanol.

[0017] As an embodiment of the present invention, in step S1, the particle size of the micron-sized SiC particles is 1-20 μm, the particle size of the submicron-sized SiC particles is 0.2-0.4 μm, and the particle size of the nano-sized SiC particles is 50-70 nm.

[0018] As an embodiment of the present invention, in step S1, the SiC particles include, by mass percentage: 30-40% micron-sized SiC particles, 30-40% submicron-sized SiC particles, and 30-40% nano-sized SiC particles. The closer the content, the more uniform the distribution and the better the enhancement effect.

[0019] The present invention adopts micron-sized particles with larger particle sizes, and the agglomeration phenomenon thereof is weakened compared with that of small-sized nano-sized particles. In addition, by increasing the proportion of nano-sized and submicron-sized particles (40%, 30%), the "coarse-fine" distribution characteristics are more obvious, thereby significantly improving the modulus and mechanical properties of the magnesium-based composite material. The present invention uses nanometer-scale and micrometer-scale SiC reinforcement particles. During the stirring casting process, the nanometer-scale SiC particles are prone to agglomeration due to the large difference in particle size, and the dispersibility is poor. Nanometer-scale, submicrometer-scale and micrometer-scale SiC particles are ball-milled and mixed with Al powder, and a prefabricated block is obtained by cold pressing. During the preparation of the stirring casting magnesium-based composite material, a multi-level reinforcement particle distribution feature of "nanometer-submicrometer, submicrometer-micrometer" is generated. Compared with the "nanometer-micrometer" particle distribution, the three reinforcement particles of different sizes are evenly dispersed in the melt through the buffering effect of the submicrometer-scale particles preferentially agglomerating with the nanometer-scale particles. Compared with adding nanometer-scale and micrometer-scale SiC reinforcement particles at the same time, the agglomeration phenomenon is weakened, thereby improving the effect of heterogeneous structure strengthening.

[0020] As an embodiment of the present invention, in step S1, the particle size of the Al powder particles is 10 to 100 μm.

[0021] As an embodiment of the present invention, in step S1, the mass ratio of SiC particles to Al powder particles is 2: 1 to 1: 1. Using a higher Al content will result in an excessively high Al content in the alloy, a reduced elongation and an increased density.

[0022] As an embodiment of the present invention, in step S1, the rotation speed is 100-400 rpm, the ball milling time is 4-24 hours, and the ball-to-material ratio is 6:1-20:1.

[0023] If SiC particles are directly added to the melt, the wettability of the reinforcement particles to the matrix alloy is poor, resulting in poor dispersion uniformity of the reinforcement particles, leading to lower modulus and mechanical properties of the material. The present invention uses low-energy mixed powder ball milling to form a reinforcement particle pretreatment method with the characteristics of "metal carrier-core-shell structure", which improves the uniformity and wettability of the dispersion of reinforcement SiC particles in the matrix alloy, so that nano-scale, submicron-scale, and micron-scale SiC reinforcement particles are evenly distributed and dispersed, avoiding agglomeration of reinforcement particles when added, and enhancing the strengthening effect of the "coarse-fine-coarse-fine" layered heterogeneous structure characteristics, so that the magnesium-based composite material has a higher modulus while still maintaining good mechanical properties.

[0024] As an embodiment of the present invention, in step S1, the pressure of the cold pressing treatment is 50-80 MPa, and the holding time is 10-30 min. The mold used for cold pressing to prepare the composite powder prefabricated block is a stainless steel cylindrical mold. Cold pressing reduces the volume of the Al powder and SiC particle powder after ball milling mixing, and after being cold pressed into a block, it is convenient to add it to the melt during smelting.

[0025] As an embodiment of the present invention, in step S2, the smelting is carried out under a protective atmosphere.

[0026] As an embodiment of the present invention, in step S2, the SiC-Al composite powder preform is added by mixing the SiC-Al composite powder preform and Ar gas and adding them to the melt through a rotary blowing device. The flow rate of the rotary blowing Ar gas is 1.6 to 2 L / h, and the rotation speed is 200 to 400 rpm.

[0027] As an embodiment of the present invention, in step S2, while continuing to smelt, the melt is subjected to low-speed and high-speed mechanical stirring, and is supplemented with ultrasonic treatment. The low-speed stirring time is 2 to 4 minutes, the rotation speed is 200 to 400 rpm; the high-speed stirring time is 10 to 20 minutes, the rotation speed is 600 to 800 rpm; the ultrasonic treatment time is 20 to 40 minutes, and the power is 400 to 600W.

[0028] As an embodiment of the present invention, in step S3, the homogenization temperature is 400-420° C., and the insulation time is 18-20 h.

[0029] As an embodiment of the present invention, in step S3, the extrusion temperature of hot extrusion is 320-350° C., and the extrusion ratio is 16:1-25:1.

[0030] As an embodiment of the present invention, the multi-scale SiC particle heterostructure reinforced magnesium-based composite material obtained in step S3 includes, by mass percentage: Al 6-12%, Y 0.8-1.2%, SiC particles 8-12%, and the balance Mg.

[0031] If the content of Y element is increased, due to the limited solid solubility of Y element, Y element will aggregate, and the in-situ self-generated AlY2 phase cannot be obtained, and the reinforcement effect cannot be achieved.

[0032] The multi-scale SiC particle heterogeneous structure reinforced magnesium-based composite material includes, by mass percentage: Al 6-12%, Zn 0.5-2%, Y 0.8-1.2%, SiC particles 8-12%, and the balance is Mg. More preferably, Al 9%, Zn 1%, Y 1%, SiC particles 10%, and the balance is Mg.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1) The matrix alloy is Mg-9Al-1Zn-1Y. Compared with Mg-9Al-1Zn alloy (AZ91), the added Y element and Al element generate Al2Y in-situ self-generated second phase particles, which enhances the modulus and strength of the material.

[0035] 2) Due to the difference in size, micron-, submicron-, and nanometer-sized SiC particles form a heterogeneous structure due to size differences, which produces a heterogeneous structural strengthening effect. Although the plasticity is slightly reduced, its yield strength and tensile strength are improved compared to AZ91 alloy; and due to the addition of SiC particles, its modulus is greatly improved.

[0036] 3) During the vacuum melting process, the melt is stirred by rotary blowing, bell jar and ultrasonic treatment, so that the SiC particle reinforcement can be suspended inside the melt, thereby improving the dispersion and uniformity of the composite material ingot reinforcement particles, and further improving the heterogeneous structure strengthening effect of micron, submicron and nanometer SiC particles.

[0037] 4) Then, through subsequent plastic deformation, SiC particles of different sizes are further dispersed evenly, and due to the influence of the extrusion direction, the particles are arranged along the extrusion direction, and the particles show a layered distribution characteristic of "coarse, fine, coarse, fine"; among them, one layer is micron-sized SiC particles, one layer is submicron-sized SiC particles, and one layer is nano-sized SiC particles, which alternate with each other and show a layered distribution characteristic, forming a heterogeneous structure with a layered distribution characteristic, which further enhances the strengthening effect of the SiC particle heterogeneous structure, such as Figure 4 shown.

[0038] 5) Therefore, by adding the in-situ self-generated second phase generated by rare earth elements, adding multi-scale SiC particles and the subsequent plastic deformation process, the second phase strengthening, reinforcement particle strengthening and heterogeneous structure strengthening effects are produced, and the modulus and strength of the magnesium-based composite material are improved at the same time. The method can be used to prepare a magnesium-based composite material with high modulus and high strength, improve the mechanical properties of high-modulus magnesium-based composite materials, and is of great significance for expanding the application range of magnesium-based composite materials in aerospace and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0040] Figure 1 Schematic diagram of the preparation process of SiC-Al composite powder prefabricated blocks.

[0041] Figure 2 Young's modulus and density of the magnesium-based composite material prepared in the present invention.

[0042] Figure 3 The room temperature mechanical properties of the magnesium-based composite material prepared by the present invention.

[0043] Figure 4 This is a metallographic picture of the magnesium-based composite material prepared in Example 3 of the present invention;

[0044] Figure 5 This is a microstructure picture of the magnesium-based composite material prepared in Example 3 of the present invention, perpendicular to the extrusion direction. DETAILED DESCRIPTION

[0045] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0046] Example 1

[0047] This embodiment relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, in which the mass percentages of the components are respectively Al: 9%, Zn: 1%, Y: 1%, SiC particles: 10%, and the balance is Mg. The diameters of the multi-scale SiC particles used are respectively: micron: 20 μm, submicron: 0.4 μm, nanometer: 70 nm, and the diameter of the micron Al powder used is 100 μm.

[0048] The preparation method of the multi-scale SiC particle heterostructure reinforced magnesium-based composite material is as follows:

[0049] 1) Using ultrasonic cleaning equipment, micron-sized, submicron-sized and nano-sized SiC particles and micron-sized Al powder are ultrasonically cleaned in anhydrous ethanol to fully remove oil stains, impurities and oxides on the surface of the particles, and then filtered and dried.

[0050] 2) SiC particles of different particle sizes were ball-milled with Al powder on a planetary ball mill to prepare SiC-Al mixed powder. The mass ratio of the mixed powder was SiC:Al=2:1, wherein the mass percentages of micron-sized, submicron-sized and nanometer-sized SiC particles were 30%, 30% and 40% respectively; the rotation speed was 400 rpm, the ball-milling time was 4 h, and the ball-to-material ratio was 10:1.

[0051] 3) The mixed powder prepared by ball milling micron-sized, submicron-sized and nano-sized SiC particles and Al powder is cold pressed; a stainless steel cylindrical mold is used to add the ball-milled mixed powder into the mold for cold pressing. The cold pressing pressure is 50 MPa and the pressure is maintained for 30 minutes to obtain SiC-Al composite powder preforms of different particle sizes for subsequent smelting and preparation of magnesium-based composite materials. Figure 1 Schematic diagram of the preparation process of multi-scale SiC-Al composite powder preform blocks for preparing magnesium-based composite materials according to the present invention.

[0052] 4) Melting process under protective atmosphere: Melting is carried out in a vacuum melting furnace. First, magnesium, Al, zinc, magnesium The yttrium master alloy is melted in proportion under a protective atmosphere, and then stirred at 680°C for 5 minutes; then, the SiC-Al composite powder preform and Ar gas are mixed and added to the melt through a rotary blowing device, the Ar gas flow rate is 2L / h, the rotation speed is 400rpm, and a bell jar is used to cover it and stir it so that the particle reinforcement can be suspended inside the melt; secondly, the composite powder preform is added, and the melt is mechanically stirred and ultrasonically treated by a stirring device in a vacuum melting furnace, specifically: first low-speed stirring for 6 minutes, a rotation speed of 400rpm, then high-speed stirring for 20 minutes, a rotation speed of 800rpm, and then ultrasonic treatment for 40 minutes, with a power of 600W; finally, when the temperature rises to 720°C, it is poured into a steel mold to obtain a composite material ingot.

[0053] 5) The composite material ingot was homogenized and hot extruded, with a homogenization temperature of 420°C, a holding time of 20 h, an extrusion temperature of 350°C, and an extrusion ratio of 25:1.

[0054] The modulus of the modified multi-scale SiC particle reinforced magnesium-based composite material prepared according to Example 1 is 57 GPa and the density is 1.83 g / cm 3 ,like Figure 2 As shown; the room temperature mechanical properties are: yield strength 231MPa, tensile strength 343MPa, elongation 8.6%, as shown Figure 3 The test specimens and methods for tensile properties are based on the standard GB / T228.1-2010, and the test specimens and methods for density and elastic modulus are based on the standard GB / T22315-2008.

[0055] Example 2

[0056] This embodiment relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, in which the mass percentages of the components are respectively Al: 9%, Zn: 1%, Y: 1%, SiC particles: 10%, and the balance is Mg. The diameters of the multi-scale SiC particles used are respectively: micron: 1 μm, submicron: 0.2 μm, nanometer: 50 nm, and the diameter of the micron Al powder used is 100 μm.

[0057] The preparation method of the multi-scale SiC particle heterostructure reinforced magnesium-based composite material is as follows:

[0058] 1) Using ultrasonic cleaning equipment, micron-sized, submicron-sized and nano-sized SiC particles and micron-sized Al powder are ultrasonically cleaned in anhydrous ethanol to fully remove oil stains, impurities and oxides on the surface of the particles, and then filtered and dried.

[0059] 2) SiC particles of different particle sizes were ball-milled with Al powder on a planetary ball mill to prepare SiC-Al mixed powder. The mass ratio of the mixed powder was SiC:Al=2:1, wherein the mass percentages of micron-sized, submicron-sized and nanometer-sized SiC particles were 30%, 30% and 40% respectively; the rotation speed was 400 rpm, the ball-milling time was 4 h, and the ball-to-material ratio was 10:1.

[0060] 3) The mixed powder prepared by ball milling micron-sized, submicron-sized and nano-sized SiC particles and Al powder is cold pressed; a stainless steel cylindrical mold is used to add the ball-milled mixed powder into the mold for cold pressing. The cold pressing pressure is 50 MPa and the pressure is maintained for 30 minutes to obtain SiC-Al composite powder preforms of different particle sizes for subsequent smelting and preparation of magnesium-based composite materials. Figure 1 Schematic diagram of the preparation process of multi-scale SiC-Al composite powder preform blocks for preparing magnesium-based composite materials according to the present invention.

[0061] 4) Melting process under protective atmosphere: Melting is carried out in a vacuum melting furnace. First, magnesium, Al, zinc, magnesium The yttrium master alloy is melted in proportion under a protective atmosphere, and then stirred at 680°C for 5 minutes; then, the SiC-Al composite powder prefabricated block and Ar gas are mixed and added to the melt through a rotary blowing device, the Ar gas flow rate is 1.6L / h, the rotation speed is 200rpm, and a bell jar is used to cover it and stir it so that the particle reinforcement can be suspended inside the melt; secondly, the composite powder prefabricated block is added, and the melt is mechanically stirred and ultrasonically treated by a stirring device in a vacuum melting furnace, specifically: first low-speed stirring for 2 minutes, rotation speed 200rpm, then high-speed stirring for 10 minutes, rotation speed 600rpm, and then ultrasonic treatment for 20 minutes, power 400W; finally, when the temperature rises to 720°C, it is poured into a steel mold to obtain a composite material ingot.

[0062] 5) The composite material ingot was homogenized and hot extruded, with a homogenization temperature of 420°C, a holding time of 20 h, an extrusion temperature of 350°C, and an extrusion ratio of 25:1.

[0063] The modulus of the modified multi-scale SiC particle reinforced magnesium-based composite material prepared according to Example 2 is 61 GPa and the density is 1.84 g / cm 3 ,like Figure 2 As shown; the room temperature mechanical properties are: yield strength 238MPa, tensile strength 385MPa, elongation 5.6%, as shown Figure 3 The test specimens and methods for tensile properties are based on the standard GB / T228.1-2010, and the test specimens and methods for density and elastic modulus are based on the standard GB / T22315-2008.

[0064] Example 3

[0065] This embodiment relates to a method for preparing a multi-scale SiC particle heterogeneous structure reinforced magnesium-based composite material, in which the mass percentages of the components are respectively Al: 9%, Zn: 1%, Y: 1%, SiC particles: 10%, and the balance is Mg. The diameters of the multi-scale SiC particles used are respectively: micron: 1 μm, submicron: 0.4 μm, nanometer: 50 nm, and the diameter of the micron Al powder used is 100 μm.

[0066] The preparation method of the multi-scale SiC particle heterostructure reinforced magnesium-based composite material is as follows:

[0067] 1) Using ultrasonic cleaning equipment, micron-sized, submicron-sized and nano-sized SiC particles and micron-sized Al powder are ultrasonically cleaned in anhydrous ethanol to fully remove oil stains, impurities and oxides on the surface of the particles, and then filtered and dried.

[0068] 2) SiC particles of different particle sizes were ball-milled with Al powder on a planetary ball mill to prepare SiC-Al mixed powder. The mass ratio of the mixed powder was SiC:Al=2:1, wherein the mass percentages of micron-sized, submicron-sized and nanometer-sized SiC particles were 30%, 30% and 40% respectively; the rotation speed was 400 rpm, the ball-milling time was 4 h, and the ball-to-material ratio was 10:1.

[0069] 3) The mixed powder prepared by ball milling micron-sized, submicron-sized and nano-sized SiC particles and Al powder is cold pressed; a stainless steel cylindrical mold is used to add the ball-milled mixed powder into the mold for cold pressing. The cold pressing pressure is 50 MPa and the pressure is maintained for 30 minutes to obtain SiC-Al composite powder preforms of different particle sizes for subsequent smelting and preparation of magnesium-based composite materials. Figure 1 Schematic diagram of the preparation process of multi-scale SiC-Al composite powder preform blocks for preparing magnesium-based composite materials according to the present invention.

[0070] 4) Melting process under protective atmosphere: Melting is carried out in a vacuum melting furnace. First, magnesium, Al, zinc, magnesium The yttrium master alloy is melted in proportion under a protective atmosphere, and then stirred at 680°C for 5 minutes; then, the SiC-Al composite powder preform and Ar gas are mixed and added to the melt through a rotary blowing device, the Ar gas flow rate is 1.8L / h, the rotation speed is 300rpm, and a bell jar is used to cover it and stir it so that the particle reinforcement can be suspended inside the melt; secondly, the composite powder preform is added, and the melt is mechanically stirred and ultrasonically treated by a stirring device in a vacuum melting furnace, specifically: first low-speed stirring for 4 minutes, a rotation speed of 300rpm, then high-speed stirring for 15 minutes, a rotation speed of 700rpm, and then ultrasonic treatment for 30 minutes, with a power of 500W; finally, when the temperature rises to 720°C, it is poured into a steel mold to obtain a composite material ingot.

[0071] 5) The composite material ingot was homogenized and hot extruded, with a homogenization temperature of 420°C, a holding time of 20 h, an extrusion temperature of 350°C, and an extrusion ratio of 25:1.

[0072] The modulus of the modified multi-scale SiC particle reinforced magnesium-based composite material prepared according to Example 3 is 62 GPa and the density is 1.88 g / cm 3 ,like Figure 2 As shown; the room temperature mechanical properties are: yield strength 242MPa, tensile strength 390MPa, elongation 4.7%, as shown Figure 3The tensile test specimen and method are in accordance with the standard GB / T228.1-2010, and the density and elastic modulus test specimen and method are in accordance with the standard GB / T22315-2008. The metallographic image of the magnesium-based composite material prepared in Example 3 of the present invention is shown in FIG. Figure 4 As shown in the figure, the black particles are micron-sized SiC particles. If you continue to zoom in, you will find black submicron-sized and nano-sized particles, which show a "coarse-fine" layered distribution along the extrusion direction. The structure of the magnesium-based composite material perpendicular to the extrusion direction is shown in the figure. Figure 5 shown.

[0073] Comparative Example 1

[0074] This comparative example relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, which is basically the same as Example 1, except that: no Y element is included, and the SiC particles account for 11%.

[0075] The magnesium-based composite material prepared by this method has a yield strength of 202MPa, a tensile strength of 316MPa, an elongation of 10.2%, an elastic modulus of 55GPa, and a density of 1.83g / cm 3 .

[0076] It can be concluded from the experimental data of Comparative Example 1 that, although the SiC particles are increased to ensure the content of the reinforcing phase, the overall performance of the magnesium-based composite material is reduced due to the lack of the synergistic effect of the Y element.

[0077] Comparative Example 2

[0078] This comparative example relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, which is basically the same as Example 1, except that SiC particles of different particle sizes and Al powder are not prepared into prefabricated blocks, but are directly added to the melt.

[0079] The magnesium-based composite material prepared by this method has a yield strength of 212MPa, a tensile strength of 328MPa, an elongation of 6.5%, an elastic modulus of 53GPa, and a density of 1.82g / cm 3 .

[0080] It can be concluded from the experimental data of Comparative Example 2 that direct addition of SiC particles results in poor dispersion, aggregation of SiC particles, and degradation of material properties.

[0081] Comparative Example 3

[0082] This comparative example relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, which is basically the same as Example 1, except that the mass percentages of micron-sized, submicron-sized and nanometer-sized SiC particles are 40%, 10% and 50% respectively.

[0083] The magnesium-based composite material prepared by this method has a tensile strength of 219MPa, a yield strength of 332MPa, an elongation of 5.8%, an elastic modulus of 56GPa, and a density of 1.85g / cm 3 .

[0084] The mechanical properties of the composite material in this comparative example are reduced, and the possible reason is that: the content of submicron SiC particles is small, resulting in a poor transition between the "coarse and fine" layered structures, poor heterogeneous structure strengthening effect, and affecting the performance of the material.

[0085] Comparative Example 4

[0086] This comparative example relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, which is basically the same as Example 1, except that the mass percentages of micron-sized, submicron-sized and nanometer-sized SiC particles are 15%, 15% and 70% respectively.

[0087] The magnesium-based composite material prepared by this method has a yield strength of 211 MPa, a tensile strength of 338 MPa, an elongation of 5.2%, an elastic modulus of 53 GPa, and a density of 1.86 g / cm 3 .

[0088] The mechanical properties of the composite material in this comparative example are reduced, and the reason may be that the content of micron- and submicron-sized SiC particles is small, and the difference with the content of nano-sized SiC is large, resulting in unclear "coarse and fine" layered structures, poor heterogeneous structural reinforcement effect, and affecting the performance of the material.

[0089] Comparative Example 5

[0090] This comparative example relates to a method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, which is basically the same as Example 1, except that the Y element is replaced by the Gd element.

[0091] The magnesium-based composite material prepared by this method has a yield strength of 216MPa, a tensile strength of 322MPa, an elongation of 6.3%, an elastic modulus of 54GPa, and a density of 1.85g / cm 3 .

[0092] The Y element is replaced by the Gd element, but the Gd element is easy to agglomerate, the generated Al2Gd phase is small, and the enhancement effect is not obvious.

[0093] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material, characterized in that: The steps include: S1, ball-milling and mixing micron-sized, submicron-sized and nanometer-sized SiC particles with Al powder particles to obtain SiC-Al mixed powder, and then cold-pressing to obtain SiC-Al composite powder prefabricated blocks; S2, weighing other raw materials according to the alloy ratio, smelting, adding the SiC-Al composite powder prefabricated block into the smelted melt to continue smelting, and then casting to obtain a composite material ingot; the other raw materials include Mg single substance, Al single substance, and Mg-Y master alloy; S3. The composite material ingot is homogenized and hot extruded to obtain a multi-scale SiC particle heterostructure reinforced magnesium-based composite material.

2. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S1, the particle size of the micron-sized SiC particles is 1 to 20 μm, the particle size of the submicron-sized SiC particles is 0.2 to 0.4 μm, and the particle size of the nano-sized SiC particles is 50 to 70 nm; And / or, in step S1, the particle size of the Al powder particles is 10 to 100 μm.

3. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S1, the SiC particles include, by mass percentage, 30-40% of micron-sized SiC particles, 30-40% of submicron-sized SiC particles, and 30-40% of nano-sized SiC particles.

4. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S1 , the mass ratio of SiC particles to Al powder particles is 2:1 to 1:

1.

5. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S1, the rotation speed is 100-400 rpm, and the ball milling time is 4-24 hours.

6. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S1, the pressure of the cold pressing treatment is 50 to 80 MPa, and the holding time is 10 to 30 minutes.

7. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S2, the SiC-Al composite powder preform is added by mixing the SiC-Al composite powder preform and Ar gas and adding the mixture into the melt through a rotary blowing device.

8. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S2, while continuing to smelt, the melt is subjected to low-speed mechanical stirring, high-speed mechanical stirring, and then ultrasonic treatment in sequence; The low-speed stirring time is 2 to 4 minutes, and the rotation speed is 200 to 400 rpm; the high-speed stirring time is 10 to 20 minutes, and the rotation speed is 600 to 800 rpm; the ultrasonic treatment time is 20 to 40 minutes, and the power is 400 to 600W.

9. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: In step S3, the homogenization temperature is 400-420°C and the holding time is 18-20h; And / or, in step S3, the extrusion temperature of hot extrusion is 320-350° C., and the extrusion ratio is 16:1-25:

1.

10. The method for preparing a multi-scale SiC particle heterostructure reinforced magnesium-based composite material according to claim 1, characterized in that: The multi-scale SiC particle heterogeneous structure reinforced magnesium-based composite material obtained in step S3 includes, by mass percentage, 6-12% Al, 0.8-1.2% Y, 8-12% SiC particles, and the remainder Mg.

Citation Information

Patent Citations

  • High-strength high-modulus magnesium-based composite material containing SiC particles

    CN104313442A

  • SiC particle-reinforced AZ91 magnesium-based composite material, preparation method and application thereof and radiator shell

    CN110129608A

  • Preparation method of in-situ synthesis Al2Y reinforced fine-grain magnesium-based composite material

    CN118222869A

  • Magnesium-based composite material synergistically reinforced by nano metal particles and ceramic particles and preparation method of magnesium-based composite material

    CN118531278A

  • Metal matrix composite

    US20040173291A1

Cited By

  • Heat-resistant cyclic wear-resistant aluminum-based composite material and preparation method thereof

    CN120443027A

  • Multi-scale TiC particle reinforced large-thickness abrasion-resistant steel and preparation method thereof

    CN120796858A